2012
DOI: 10.1080/02701367.2012.10599858
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Kinase Activity Weakly Correlates to Volume Completed Following Upper Body Resistance Exercise

Abstract: In the current study, we examined the relationship between serum creatine kinase (CK) activity following upper body resistance exercise with a 1- or 3-min rest between sets. Twenty men performed two sessions, each consisting of four sets with a 10-repetition maximum load. The results demonstrated significantly greater volume for the 3-min condition (M = 4156 kg, SD = 867, for 3 min; vs. M = 3503 kg SD = 759, for 1 min; p < .001), with no significant differences in delta CK activity between conditions (p = .574… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In contrast, following a 30 minute single leg eccentric step exercise protocol, Fredsted, Clausen (10) reported CK and maximal torque loss to be significantly lower in males compared to females. The aforementioned discrepancies may be attributed to differences in exercise volume [ 15 ] and/or different muscle architecture and tendon properties, for example in the elbow flexors compared to the knee extensors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, following a 30 minute single leg eccentric step exercise protocol, Fredsted, Clausen (10) reported CK and maximal torque loss to be significantly lower in males compared to females. The aforementioned discrepancies may be attributed to differences in exercise volume [ 15 ] and/or different muscle architecture and tendon properties, for example in the elbow flexors compared to the knee extensors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [41,42] have shown a moderate positive correlation (r = 0.44) between CK-MM levels and VL. Nosaka and Clarkson [43] measured muscle volume involved in (unilateral or bilateral) strength exercise with the same VL and found similar increase in CK levels.…”
Section: Discussionmentioning
confidence: 98%
“…While CK does moderately correlate (r = 0.45 to 0.55, p = 0.01 to 0.05) to the amount of resistance training volume performed (Machado et al, 2012), this correlation may not be indicative of how much volume can or should be performed. Specifically, the causative relationship between adaptive skeletal muscle remodelling and muscle damage is disputed (Damas et al, 2016).…”
Section: Muscle Damage Biomarkersmentioning
confidence: 88%